RARE GAS SYSTEMATICS AND THE ORIGIN OF OCEANIC ISLANDS: THE KEY ROLE OF ENTRAINMENT AT THE 670 KM BOUNDARY LAYER - Allère C.J.; Moreira M. (My University, 2004)
Using the best estimates of rare gas isotopic ratios for both Oceanic Island Basalts (OIB) and Mid Oceanic Ridge Basalts (MORB) sources, and knowing the incompatible element ratios between these two sources (e.g. K, U), it is therefore possible to determine the ratios between the concentrations of non-radiogenic isotopes (3He, 22Ne, 36Ar) in the lower mantle and the upper mantle. The calculations suggest that He, Ne and Ar are enriched by 500 in the lower mantle. Therefore, even a small amount of entrainment of lower layer material in a starting mantle plume can change the isotopic ratios of the plume, producing OIB signatures distinct and more variable than MORB, as is actually observed. Unless the lower mantle is strongly heterogeneous for rare gases, the source of OIB is certainly the 670 km thermal boundary layer, rather than the core–mantle boundary.